LAPAROSCOPIC OVARIAN DRILLING FOR POLYCYSTIC OVARIAN SYNDROME: TREATMENT OUTCOME - Hameed, Nazli; Ali, Muhammad Asghar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Anovulatory infertility due to polycystic ovarian syndrome (PCOS) remains the commonest cause among women of reproductive age group. Although clomiphene citrate (CC) remains the first choice treatment in addition to other medical therapies, laparoscopic ovarian drilling (LOD) is rapidly gaining acceptance as a second line management in patients who failed to respond to CC. This study was done to evaluate the efficacy of LOD in management of PCOS related infertility. Methods: This was a descriptive study conducted at CMH Peshawar, CMH Kharian, and PAF Hospital Mushaf, from 2004 to 2011. It included 69 patients who underwent LOD for anovulatory infertility after being diagnosed as PCOS. Patients were diagnosed on the basis of their clinical, hormonal and ultrasonic findings. Age of the patients, features suggestive of hyperandrogenism, body mass index (BMI), duration of infertility, and LH/FSH ratio were noted. Patients were followed post-operatively for one year. Results: Overall ovulation rate was 82.61% after LOD. Thirty-one out of 69 patients ovulated spontaneously within first 6 weeks after LOD while 26 patients ovulated on getting treatment with CC in addition to LOD. Thirty-three (47.82%) patients conceived in their first year after surgery. About 54% of patients reported improvement in their symptoms related to hyperandrogenism. Conclusion: LOD is an established and safe method as a second line treatment for PCOS related infertility. Keywords: Polycystic Ovarian Syndrome, Laparoscopic ovarian drilling